1995
DOI: 10.1002/dvg.1020170108
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, sequencing, and expressional analysis of the chick homologue of follistatin

Abstract: Follistatin, a secreted glycoprotein, has been shown to act as a potent neural inducer during early amphibian development. The function of this protein during embryogenesis in higher vertebrates is unclear, and to further our understanding of its role we have cloned, sequenced, and performed an in-depth expressional analysis of the chick homologue of follistatin. In addition we also describe the expression pattern of activin beta A and activin beta B, proteins that have previously been shown to be able to inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 32 publications
4
21
0
Order By: Relevance
“…In stage-12 − chicks, activin-␤B expression is detectable in notochord tissue but not in more lateral mesoderm (Fig. 4A), confirming previous work (Connolly et al 1995). Activin-␤A expression is not detected at this stage (Connolly et al 1995; data not shown).…”
Section: Notochord Factors Activin and Fgf Initiate Pancreatic Differsupporting
confidence: 89%
“…In stage-12 − chicks, activin-␤B expression is detectable in notochord tissue but not in more lateral mesoderm (Fig. 4A), confirming previous work (Connolly et al 1995). Activin-␤A expression is not detected at this stage (Connolly et al 1995; data not shown).…”
Section: Notochord Factors Activin and Fgf Initiate Pancreatic Differsupporting
confidence: 89%
“…Goldfish follistatin exhibits as much as 95% sequence identity with that of zebrafish (Bauer et al 1998) and about 75% with the homologous protein of other vertebrates (Inouye et al 1991, Tashiro et al 1991, Connolly et al 1995, suggesting conserved functions of this protein in vertebrates. In mammals and birds, Figure 5 Effects of recombinant human follistatin (100 ng/ml) and recombinant goldfish follistatin (50 ml/ml) on the expression of follistatin, FSHb, and LHb in the cultured pituitary cells.…”
Section: Discussionmentioning
confidence: 99%
“…from the neural folds prior to NT closure and later from the roof plate). Among these are members of the TGFβ family, including activin, Bmp4 and Bmp7 (Connolly et al, 1995;Liem et al, 1997;Liem et al, 1995;Tam, 2001). The expression of these TGFβ family proteins in the neural plate at early developmental stages is in close proximity to migrating kidney IM precursor cells (James and Schultheiss, 2003) (Fig.…”
Section: Identifying the Source Tissue Of The Kidneyinductive Signalsmentioning
confidence: 99%
“…Activin is also expressed in the neural plate of stage 5-8 embryos (Connolly et al, 1995), which, at these stages, is in immediate contact with migrating kidney precursor cells. Limited evidence exists for the involvement of activin in early kidney induction.…”
Section: Activin-like Signaling Is Required But Insufficient For Kidnmentioning
confidence: 99%